A 2-D imaging-assisted geometrical transformation method for non-destructive evaluation of the volume and surface area of avian eggs. (June 2020) - Narushin, Valeriy G.; Lu, Gang; Cugley, James; Romanov, Michael N.; Griffin, Darren K.
Abstract: Egg volume and surface area are reliable predictors of quality traits for both table and hatching chicken eggs. A new non-destructive technique for the fast and accurate evaluation of these two egg variables is addressed in the present study. The proposed method is based on the geometrical transformation of actual egg contour into a well-known geometrical figure which shape most of all resembles the examined egg. The volume and surface area of an examined egg were recomputed using the formulae appropriate for three figures including sphere, ellipsoid, and egg-shape ovoid. The method of the geometrical transformation includes the measurements of the egg length and the area of the examined eggs. These variables were determined using two-dimensional (2-D) digital imaging and image processing techniques. The geometrical transformation approach is proven to be reliable to turn the studied chicken eggs into the three chosen ovoid models, with the best prediction being shown for the ellipsoid and egg-shape ovoid, whilst the former was slightly more preferable. Depending on the avian species studied, we hypothesise that it would be more suitable to use the sphere model for more round shaped eggs and the egg-shaped ovoid model if the examined eggs are more conical. The choice of the proposed transformation technique would be applicable not only for the needs of poultry industry but also in ornithological, basically zoological studies when handling the varieties of eggs of different shapes. The experimental results show that the method proposed is accurate, reliable, robust and fast when coupled and assisted with the digital imaging and image processing techniques, and can serve as a basis for developing an appropriate instrumental technology and bringing it into the practice of poultry enterprises and hatcheries. Highlights: Egg volume and surface area are valuable predictors of egg quality traits. A method of geometrical transformation of an egg contour into a geometrical figure was examined. Theoretical dependence between egg volume and surface area was studied. 2-D (two-dimensional) digital imaging and image processing techniques were applied. The elaborated method showed a correlation coefficient of 0.96 and standard error of 2.14%.